Uso de marketing digital en microempresas de comida rápida de la ciudad de Machala a consecuencia del COVID 19. - Villamar Hurtado, Nathaly Elizabeth; Yaguana Madrid, Anthony Josue (My University, 2021)
The Covid-19 pandemic has brought changes in the business model of companies and digital marketing has become a fundamental part for them to develop strategies that promote the sale of products, considering the use of social networks as the main factor. Within social networks there are different tools that facilitate the management and development of each of them. For this reason, the research carried out is based on the analysis of the tools of social networks. For the optimal compilation of the information, a qualitative-exploratory research was carried out where interviews were conducted with 3 micro-entrepreneurs of fast food from the City of Machala, who provided the necessary information about the use of digital marketing with respect to social networks, where it was observed that digital marketing is important for business development as it allows greater communication with customers and this in turn generates benefits for the company.
La pandemia del Covid-19 ha traído cambios en el modelo de negocio de las empresas y el marketing digital se ha vuelto parte fundamental para que desarrollen estrategias que promuevan la venta de productos, considerando el uso de las redes sociales como factor principal. Dentro de las redes sociales se encuentran distintas herramientas que facilitan el manejo y desarrollo de cada una de ellas. Por ello la investigación realizada se basa en el análisis de las herramientas de las redes sociales. Para la óptima recopilación de la información se llevó a cabo una investigación cualitativa-exploratoria donde se realizó entrevistas a 3 microempresarios de comida rápida de la Ciudad de Machala los mismos que brindaron información necesaria acerca del uso del marketing digital con respecto a las redes sociales, donde se observó que el marketing digital es importante para el desarrollo empresarial ya que permite tener una mayor comunicación con los clientes y esto a su vez genera beneficios para la empresa.
Keywords: MARKETING DIGITAL; REDES SOCIALES; HERRAMIENTAS; COVID-19